Taenia solium cysticercosis [ from basic to clinical science - Prabhakar, S. [ (Sudesh)]; Singh, G. [ (Gagandeep)] (CABI, 2002)
Taenia solium cysticerosis is a parasitic disease caused by the dissemination of the larval form of the pork tapeworm. This book covers basic science, epidemiology, clinical aspects, pathology, investigational aspects of neurocysticercosis and therapy ad prevention.